Cognitive function and cardiovascular health in the elderly: network analysis based on hypertension, diabetes, cerebrovascular disease, and coronary heart disease - Wang, Yucheng; Zhang, Huanrui; Liu, Linzi; Li, Zijia; Zhou, Yang; Wei, Jiayan; Xu, Yixiao; Zhou, Yifang; Tang, Yanqing (Frontiers in Aging Neuroscience, 2023)
This study employed a network analysis approach to examine the relationship between cognitive function and cardiovascular health in older adults, focusing on four vascular factors: hypertension, diabetes, cerebrovascular disease, and coronary heart disease. A cross-sectional sample of 2225 eligible individuals (mean age 72.44 ± 9.63 years, 51.8% male) was recruited from Liaoning Province, China, between September 2018 and June 2022. Cognitive function was evaluated using a modified Chinese version of the MMSE scale, and network modeling was conducted to estimate the strength centrality and edge weights. By comparing the network structure of cognitive function across subgroups, incorporating vascular factors as subgroup variables while controlling for co-morbidities and confounders, the study revealed that the prevalence of these diseases exerted varying degrees of influence on different cognitive domains. Notably, cerebrovascular disease and coronary heart disease showed more significant effects on the network structure of cognitive function. These findings have implications for screening and personalized interventions targeting cognitive function in future populations.